Scaffolding Critical Reading - Corrigan, Paul T. (Teaching and Learning Inquiry, 2023)
Teachers in any discipline where reading matters should practice a robust scaffolding pedagogy to teach critical reading, in contrast to the more common but less direct approaches that often leave students to learn or not learn these skills themselves. In this essay, I describe how to adapt established methods for teaching writing (including templates) to teaching reading. To answer critics who might find the approach too “reductive,” I turn to scaffolding theory, which calls for purposefully—but temporarily—reductive teaching. Finally, I present qualitative and quantitative evidence from three years of an American literature course to show how a scaffolding approach can help students read critically.